Evaluations of Prevention Programs for Sexual, Dating, and Intimate Partner Violence for Boys and Men: A Systematic Review. (July 2021) - Graham, Laurie M.; Embry, Venita; Young, Belinda-Rose; Macy, Rebecca J.; Moracco, Kathryn E.; Reyes, Heather Luz McNaughton; Martin, Sandra L.
Among violence prevention educators and researchers, there is growing interest in sexual, dating, and intimate partner violence (SV/DV/IPV) prevention programs for males because of evidence showing that boys and men are more likely than girls and women to perpetrate SV as well as more severe forms of DV/IPV. To date, comprehensive guidance on the content, structure, delivery, and effectiveness of such programs is limited. We reviewed randomized controlled studies that evaluated SV/DV/IPV perpetration prevention programs for boys and men. Searches yielded 5, 249 potential documents for review of which 10 met inclusion criteria—representing 9 unique studies of 7 distinct programs. Two reviewers independently reviewed and abstracted data from these studies regarding program setting and target audience; type of violence addressed; number and length of program sessions; program duration, topics, activities, and delivery mode; and implementer details. Study characteristics were also examined (sample size, participant characteristics, recruitment, randomization, comparison/control condition, data collection protocols, attrition, measures of violence perpetration, and perpetration findings). The Cochrane Risk of Bias Tool was used to assess study design quality. Results show considerable heterogeneity among program content and delivery strategies, study designs, and outcome measurement. Study sample size ranged widely, and most used cluster-randomized designs, recruited undergraduate college students, and evaluated a multisession program delivered via group sessions. Only one program reduced men's self-reported SV perpetration. Accordingly, critical gaps exist around "what works" for SV/DV/IPV perpetration prevention programs for boys and men.